2007
DOI: 10.1080/08927010701315089
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and diversity of barnacles on international ships visiting Osaka Bay, Japan, and the risk of their introduction

Abstract: The occurrence and diversity of barnacles attached to the hulls of two intercontinental bulk carriers were studied at the port in Osaka Bay, Japan, to assess the potential risk of introduction of exotic species to the inner part of the bay. Barnacles were sampled from the bulbous bows, near the midship draft marks, and around the propeller posts and rudders. Twenty-two species were found, with 14 of these not previously recorded in Osaka Bay, including four species not previously recorded elsewhere in Japan. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…As such, the average operating speed of a vessel would likely have an influence on the composition of the resident biofouling community present, both at its inception and throughout its developmental growth. For example, faster vessels are likely to 'select for' biofouling communities tolerant of greater hydrodynamic forces (eg hard, solitary, encrusting taxa), while slower vessel assemblages would likely be dominated by soft, colonial, erect taxa (Coutts 1999;Otani et al 2007;Davidson et al 2009;Sylvester and MacIsaac 2009). Given this, the propensity for speed to reduce the inoculum pressure (biomass, abundance and/or richness) of any given biofouling community would likely be less than observed in this study, as the biofouling present has already been 'selected' for suitability to that vessels particular operating parameters and mode of use.…”
Section: Voyage Speed and Morphologymentioning
confidence: 99%
“…As such, the average operating speed of a vessel would likely have an influence on the composition of the resident biofouling community present, both at its inception and throughout its developmental growth. For example, faster vessels are likely to 'select for' biofouling communities tolerant of greater hydrodynamic forces (eg hard, solitary, encrusting taxa), while slower vessel assemblages would likely be dominated by soft, colonial, erect taxa (Coutts 1999;Otani et al 2007;Davidson et al 2009;Sylvester and MacIsaac 2009). Given this, the propensity for speed to reduce the inoculum pressure (biomass, abundance and/or richness) of any given biofouling community would likely be less than observed in this study, as the biofouling present has already been 'selected' for suitability to that vessels particular operating parameters and mode of use.…”
Section: Voyage Speed and Morphologymentioning
confidence: 99%
“…A recent study of Elkhorn Slough, California, revealed the presence of numerous invasive taxa present elsewhere along the west coast, despite the absence of any commercial ports (Wasson et al 2001), and fouling of recreational boats is probably a major vector for the movement of species between such habitats (Floerl & Inglis 2005). Fouling has been implicated in the global expansion of numerous invasive taxa, including crustaceans (Zardus & Hadfield 2005, Otani et al 2007), bryozoans (Marchini et al 2007), mollusks (Ricciardi 1998) and tunicates (Bullard et al 2007). We suggest that this vector may be playing a central role in the expansion of the range of Nematostella vectensis in the eastern Pacific Ocean.…”
Section: Dispersal and Range Expansion Of Nematostella Vectensismentioning
confidence: 99%
“…One such macrofouler is the barnacle Balanus amphitrite (Amphibalanus amphitrite) (Clare and Høeg 2008), which is a common member of coastal fouling communities and has an extremely wide geographical distribution (Otani et al 2007). Several studies have suggested that cypris larvae of B. amphitrite prefer to settle on surfaces of high wettability (Rittschof and Costlow 1989;Gerhart et al 1992;Holm et al 1997).…”
Section: Introductionmentioning
confidence: 99%